2020
DOI: 10.3390/molecules25133048
|View full text |Cite
|
Sign up to set email alerts
|

Towards Robust Delivery of Antimicrobial Peptides to Combat Bacterial Resistance

Abstract: Antimicrobial peptides (AMPs), otherwise known as host defence peptides (HDPs), are naturally occurring biomolecules expressed by a large array of species across the phylogenetic kingdoms. They have great potential to combat microbial infections by directly killing or inhibiting bacterial activity and/or by modulating the immune response of the host. Due to their multimodal properties, broad spectrum activity, and minimal resistance generation, these peptides have emerged as a promising response to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 177 publications
(268 reference statements)
1
65
0
Order By: Relevance
“…Peptide conjugation consists of peptide sticking, that is, the addition of polymers, such as poly(lactic-co-glycolic acid), polyvinylpyrrolidone, and polyethylene glycol, to peptides, which contributes to an improvement in bioavailability and an increase in half-life. It can also help prevent immune response and protect against degradation [ 10 , 23 ].…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide conjugation consists of peptide sticking, that is, the addition of polymers, such as poly(lactic-co-glycolic acid), polyvinylpyrrolidone, and polyethylene glycol, to peptides, which contributes to an improvement in bioavailability and an increase in half-life. It can also help prevent immune response and protect against degradation [ 10 , 23 ].…”
Section: Efforts To Overcome Peptide Limitationsmentioning
confidence: 99%
“… Peptide limitations and how to overcome them. [ 10 , 22 , 23 , 26 , 27 ]. On the left side there are four limitations to working with peptides which are in red.…”
Section: Figurementioning
confidence: 99%
“…This led us to explore bioconjugation and formulation strategies in order to mitigate these negative effects [4,60,71]. For an extensive review on these strategies, the reader is invited to consult [64] and references therein.…”
Section: Engineering Aurein 22 For Superior Activity and Bioavailabimentioning
confidence: 99%
“…Alternative approaches to minimize proteolytic cleavage include producing synthetic AMPs that incorporate D-amino acids [60], β-amino acids [61], and other non-natural amino acids [62]. The topic of improving in vivo stability has been extensively reviewed elsewhere [4,63,64], and it will not be discussed further here. In terms of toxicity, some studies have shown that the introduction of D-amino acids or the rational optimization of amphipathicity can help in lowering host toxicity [60,[65][66][67].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation